Senegalia senegal (L.) Britton Response to Microbial and Manure Amendments for the Rehabilitation of Waste Rock Dumps in the Essakane Gold Mining Site, Burkina Faso - Yonli, Hendi Hermann; Sene, Godar; Sanon, Kadidia B.; Dianda, Mahamadi; Khasa, Damase P. (Frontiers in Environmental Science, 2022)
Senegalia senegal (Fabaceae) is a widespread, multipurpose tree capable of colonizing disturbed Sub-Saharan mining sites given its adaptations to arid lands. A multi-year factorial experiment involving this species was conducted in a nursery and on waste rock dumps (Essakane gold mine, NE Burkina Faso). Inoculation with arbuscular mycorrhizal (AM) fungi (native isolate Rhizophagus aggregatus DAOM2277128; commercial isolate Rhizophagus irregularis DAOM197198) and Mesorhizobium plurifarium strain ORS3588 was conducted on S. senegal seedlings. These were planted in black polythene bags filled with three substrate types: 100% sandy soil (substrate A); 75% sandy soil, 25% manure (substrate B); and 50% sandy soil, 50% manure (substrate C). Seedlings were then out-planted on waste rock to determine whether microbial inoculation improves their growth and survival rates. Under nursery conditions, manure-enriched substrates harboured less nodulation and AM colonization, but substantially increased plant height and dry mass compared to un-amended substrate. Inoculation on manure-enrich substrates did not consistently increase root AM colonization and plant growth parameters among treatments. Plants that were inoculated with R. aggregatus alone or with R. irregularis or Mesorhizobium plurifarium ORS3588 showed the greatest increase in growth variables. On un-amended substrates, inoculation with R. aggregatus in combination with M. plurifarium or R. irregularis significantly enhanced root colonization rates, without altering plant growth parameters. Yet, inoculation with R. irregularis or M. plurifarium alone did not elicit increases in these parameters, although nodulation was greatly improved by the latter treatment. In field conditions, plant growth and survival were reduced under high rate manure amendments, likely due to less AM colonization and root nodulation that was observed for these treatments in nursery before out-planting. Strongly colonized plants on the un-amended substrate and moderately amended substrate showed greater survival after out-planting. Our results support the general conclusion that microbial inoculation and manure-enriched substrates are a viable option for mining site rehabilitation using S. senegal. They also suggest that manure amendments in forest nurseries should be cautiously applied given that high rates may impede establishment of plant symbioses, thereby affecting their performance on waste rock dumps following out-planting.